Characterization of a new bio‐based and biodegradable blends of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) and poly(butylene‐co‐succinate‐co‐adipate). Issue 19 (4th January 2022) - Le Delliou, Benjamin; Vitrac, Olivier; Castro, Mickael; Bruzaud, Stephane; Domenek, Sandra
Abstract: Melt blending of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) and poly(butylene‐co‐succinate‐co‐adipate) (PBSA) was investigated by means of batch mixing at different weight ratios (100:0, 70:30, 50:50, 30:70, and 0:100). PHBV and PBSA were immiscible. PBSA formed small nodules in PHBV, while PHBV formed large inclusions in PBSA. In 50/50 wt% blends, a co‐continuous structure was obtained. The crystallization rate of PHBV and PBSA increased in the blends, most probably due to mutual nucleation, except at the later stages, where PHBV crystallization rates slowed down inside the nodules and in the co‐continuous structure. The mechanical properties were successfully modeled with the EBM model, including parallel and serial resistances and show that the rigidity of the material can be modulated using PBSA. The elongation at break is however governed by PHBV. The blends featured brittle fracture even if PBSA was the continuous phase. The analysis of the stress at break showed that the fracture could be ascribed to debonding at the interfaces and the fracture behavior of PHBV. Abstract :